(untitled) (Research, Society and Development, 2022)
Introduction: Penile cancer, although not epidemiological, is the most incident in men. It has the specificity of affecting the man’s self-image, by reaching the genital organ, considered a symbol of male virility. Thus, in the present study, we sought from the literature: what is the scientific evidence on patients’ feelings about penectomy and coping strategies? Having as objectives: to identify the scientific evidence on the feelings of patients facing penectomy and to describe the most evident coping strategies in the literature. Method: This is a bibliographic study, an integrative literature review type. Results and Discussion: By combining the descriptors with the filters, a total sample of 3,140 articles was identified. In total, 8 articles were selected for analysis. A variety of feelings emerged in the patients’ reports such as: sadness, anger, depression, suicidal ideation, fear, low self-esteem, inferiority, shame, sadness, feeling of mutilation and loss. As a coping strategy, the search for support from the health team emerged, both from the nursing and psychological team. The encounter of a new meaning of life, with support from groups and religious. And the discovery of a new way of experiencing sexuality. Final considerations: it was observed from the analysis of the articles, that the penis removal surgery brings important psychological traumas and the health professional can help the patient to overcome the difficulties and rediscover the meaning of life after the surgery.